SISTEM KENDALI ROBOT SUMO MENGGUNAKAN BLUETOOTH BERBASIS SMARTPHONE ANDOID: SUMO ROBOT MANUAL CONTROL SYSTEM USING BLUETOOTH BASED ON ANDROID SMARTPONE - deno, denosaputra (Institut Riset dan Publikasi Indonesia, 2021)
Sports that are currently carried out are not only carried out by humans but have interfered with technology, one of which is robotics technology. One of the competitions is the sumo robot competition. The problem of making a sumo robot is making Android Smartphone applications that can be controlled remotely. And looking for the efficient use of the Hc-05 bluetooth, the purpose of making this sumo robot is that it can move manually via an Android smartphone application with a Hc-05 bluetooth connection, and can be moved to attack enemies and push enemies out of the arena, so the functionality of the robot is similar to sumo wrestlers and after that can be entered in competitions. This sumo robot uses an Arduino nano microcontroller as the brain of the sumo robot, and the Hc-05 bluetooth as a connector to an Android smartphone. . The conclusion from making this sumo robot, the robot can move according to the instructions given via a smartphone and can also avoid unwanted things, such as error sensor readings because all the movements of the sumo robot have been set by the user. Keywords: Android smartphone, Arduino nano, Bluetooth Hc-05, L298N motor driver, DC motor.